Web development recipes - Hogan, Brian P.; Warren, Chris; Weber, Mike; Johnson, Chris (Pragmatic Bookshelf, 2015)
Modern web development is so much more than just HTML and CSS with a little JavaScript mixed in. People want faster, more usable interfaces that work on multiple devices, and you need the latest tools and techniques to make that happen. This book gives you over 40 concise solutions to today's web development problems, and introduces new solutions that will expand your skill set--proven, practical advice from authors who use these tools and techniques every day. In this completely updated edition, you'll find innovative new techniques and workflows, as well as reworked solutions that take advantage of new developments.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed September 16, 2015)
Keywords: Web site development; Web sites -- Design; Sites Web; Développement; Sites Web; Conception; COMPUTERS; General; Web sites; Design